2008
DOI: 10.1038/ajh.2007.50
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of AT1 Receptor Improves Adipocyte Differentiation in Atherosclerotic and Diabetic Models

Abstract: These results suggest that enlargement and weakened differentiation of adipocytes are observed in atherosclerosis and diabetes, and that AT(1) receptor blockade prevented adipocyte enlargement and promoted adipocyte differentiation in these models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
65
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 32 publications
10
65
0
1
Order By: Relevance
“…Thus, initial in vitro experiments suggested that angiotensin II promotes preadipocyte differentiation via the AT 2 receptor (Engeli et al, 2000). Subsequently, however, it was shown that the in vivo effects of angiotensin II are mediated primarily via AT 1 and in this case the end result is expansion of adipose tissue, primarily because of adipocyte hypertrophy, and thus metabolic dysfunction (Massiéra et al, 2001, Tomono et al, 2008.…”
mentioning
confidence: 99%
“…Thus, initial in vitro experiments suggested that angiotensin II promotes preadipocyte differentiation via the AT 2 receptor (Engeli et al, 2000). Subsequently, however, it was shown that the in vivo effects of angiotensin II are mediated primarily via AT 1 and in this case the end result is expansion of adipose tissue, primarily because of adipocyte hypertrophy, and thus metabolic dysfunction (Massiéra et al, 2001, Tomono et al, 2008.…”
mentioning
confidence: 99%
“…ApoEKO mice showed an enlargement of adipocyte size. 17 In their adipose tissue, the expression of adiponectin and PPARg was lower than that of wild-type mice. These changes in ApoEKO mice were recovered by the deletion of AT 1 a receptor (AT 1 a/ApoE double KO mice).…”
Section: Angiotensin II and Adipocyte Differentiationmentioning
confidence: 95%
“…Treatment of mice with ARB decreased the plasma level of cholesterol and free fatty acids, 14,17 which is closely related with metabolic syndrome and insulin resistance.…”
Section: Metabolic Action Of Angiotensin II On Adipose Tissuementioning
confidence: 99%
See 2 more Smart Citations